Number Sense of High School Students on Real Numbers Based on Gender - Viantasari, Erwinda; Sukoriyanto, Sukoriyanto; Irawati, Santi (Universitas Suryakancana, 2024)
This research aims to describe number sense of high school students on real numbers based on gender. This type of research is descriptive qualitative. The research was conducted in class XI (consists of 36 students) of SMA Negeri 3 Malang in the even semester of the 2023/2024 academic year. The subjects are one student with male gender and one student with female gender. The subjects were selected using purposive sampling technique. The research instruments consisted of number sense tests and interview guidelines. The number sense test used consisted of five questions with each question representing the number sense indicator used. Data analysis was carried out by examining students' answers on the number sense test given and then conducting interviews with selected subjects. The result showed that the male student is able to recognize relative number size, understand the meaning of numbers, recognize the relative effect of operations on numbers, compose or decompose numbers, and judge the reasonableness of estimates of computed results. Meanwhile, the female student is only able to recognize relative number size and the relative effect of operations on numbers.